To Do or Not to Do: Dopamine, Affordability and the Economics of Opportunity - Beeler, Jeff A.; Mourra, Devry (Frontiers in Integrative Neuroscience, 2018)
Five years ago, we introduced the thrift hypothesis of dopamine, suggesting that the primary role of dopamine in adaptive behavior is regulating behavioral energy expenditure to match the prevailing economic conditions of the environment. Here we elaborate that hypothesis with several new ideas. First, we introduce the concept of affordability, suggesting that costs must necessarily be evaluated with respect to the availability of resources to the organism, which computes a value not only for the potential reward opportunity, but also the value of resources expended. Placing both costs and benefits within the context of the larger economy in which the animal is functioning requires consideration of the different timescales against which to compute resource availability, or average reward rate. Appropriate windows of computation for tracking resources requires corresponding neural substrates that operate on these different timescales. In discussing temporal patterns of dopamine signaling, we focus on a neglected form of dopamine plasticity and adaptation, changes in the physical substrate of the dopamine system itself, such as up- and down-regulation of receptors or release probability. We argue that changes in the dopamine substrate itself fundamentally alter its computational function, which we propose mediates adaptations to longer temporal horizons and economic conditions. In developing our hypothesis, we focus on dopamine D2 (D2R) receptors, arguing that D2R implements a form of 'cost control' in response to the environmental economy, serving as the 'brain's comptroller.' We propose that the balance between the direct and indirect pathway, regulated by relative expression of D1 and D2 dopamine receptors, implements affordability. Finally, as we review data, we discuss limitations in current approaches that impede fully investigating the proposed hypothesis and highlight alternative, more semi-naturalistic strategies more conducive to neuroeconomic investigations on the role of dopamine in adaptive behavior.